The incidence and predictors of overall adverse effects caused by low dose amiodarone in real-world clinical practice - Kim, Hack-Lyoung; Seo, Jae-Bin; Chung, Woo-Young; Kim, Sang-Hyun; Kim, Myung-A; Zo, Joo-Hee (The Korean journal of internal medicine, 2014)
Most current knowledge regarding amiodarone toxicity derives from clinical trials. This study was performed to investigate the incidence and risk factors of overall adverse effects of amiodarone in real-world practice using a large sample size. Between January 1, 2000 and March 10, 2012, a total of 930 consecutive patients who had been treated with amiodarone for arrhythmia were reviewed retrospectively. An amiodarone-associated adverse event was considered in cases of discontinuation or drug dose reduction due to an unexpected clinical response. The mean daily dose of amiodarone was 227 ± 126 mg, and the mean duration was 490 ± 812 days. During the mean follow-up duration of 982 ± 1,137 days, a total of 154 patients (16.6%) experienced adverse effects related to amiodarone, the most common being bradycardia or conduction disturbance (9.5%). Major organ toxicities in the thyroid (2.5%), liver (2.2%), eyes (0.6%), and lungs (0.3%) were rare. All patients recovered fully without complications after amiodarone discontinuation or dose reduction. The only independent predictor of adverse effects was the duration of amiodarone treatment (odds ratio, 1.21; 95% confidence interval, 1.03 to 1.41; p = 0.016, per year). Low-dose amiodarone is well tolerated in a real-world clinical population. Further studies with a prospective design are needed to confirm this finding.